Functional and Structural Sediment Connectivity within a Recently Burned Basin - Wester, Thad (East Carolina University, 2011)
Human populations have continued their unrelenting expansion into the wildland-urban interface and in locales which are prone to wildfire, the risk of secondary hazards associated with wildfires such as debris flows and flooding are increasing. While the implications of wildfire for the transport of sediment and surface runoff within burned areas are not agreed upon in consensus, many researchers believe an important, currently understudied aspect is the level of connectivity within the landscape. Connectivity refers to the extent to which water and sediment are or have the potential to be transferred within or between landscape compartments. The current study is designed to quantitatively capture transported sediment, assessing the level of (dis)connectivity within a recently burned basin.  Two surveys were conducted on 28-30 September 2008 (baseline topography pre-rainfall conditions) and 18-21 December 2008 (topography three days after 52mm of rainfall over a period of 22 hours) with the aid of a terrestrial laser scanner. Point clouds from the scanning sessions were used to produce 1 cm resolution DTM capturing pre- and post-rainfall topography. D-8 hydrologic networks were generated in Arc Map and used for the delineation of seven rill-gully threads (RGTs). The seven RGTs were analyzed for their pattern of deposition and erosion and their upslope contributing area sediment input.  Sediment transport was found to not be consistent for each of the RGTs and large depositional areas warranted labeling the RGTs as disconnective. We also concluded that hollows are a significant component for the connectivity of burned basins based on their importance for the routing and storage of dry ravel.
Assessment of connectivity within a recently burned basin
Keywords: Geomorphology; Connectivity; Fires; Laser scanning; Sediments; Sediment transport; Wildland-urban interface; Sedimentary basins; Wildfires; Debris avalanches; Floods